Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
DOI: 10.31274/rtd-180813-10847
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanism of mrp/plf gene expression by bFGF

Abstract: Introduction Materials and Methods Results Discussion Acknowledgments References CHARACTERIZATION OF THE MECHANISM OF mrp3 PROMOTER ACTIVATION AND THE DIFFERENTIAL RESPONSE OF THE mrp/plf PROMOTERS BY bFGF 51

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 7 publications
(7 reference statements)
2
9
0
Order By: Relevance
“…These are as follows: MMP family members; stromelysin-1 (mmp-3), gelatinase A (mmp-2), collagenase type 1, gelatinase B (92 kDa type Iv collagenase, mmp-9) and other proteases; cathepsinL, cathepsin B, tissue plasminogen activator. Furthermore the protease genes not regulated by bFGF like elastase, metalloelastase, trypsin, and chymotrypsin did not contain FRE or FRE-like sequences [313]. This was a significant finding because not only are mmp 's expressed in the same tissues as mrp/plf's but also the proteins expressed by these mmp genes are involved in similar physiological tissue remodeling events like wound healing.…”
Section: Regulation Of Gene Expression By the Fgf'smentioning
confidence: 96%
See 4 more Smart Citations
“…These are as follows: MMP family members; stromelysin-1 (mmp-3), gelatinase A (mmp-2), collagenase type 1, gelatinase B (92 kDa type Iv collagenase, mmp-9) and other proteases; cathepsinL, cathepsin B, tissue plasminogen activator. Furthermore the protease genes not regulated by bFGF like elastase, metalloelastase, trypsin, and chymotrypsin did not contain FRE or FRE-like sequences [313]. This was a significant finding because not only are mmp 's expressed in the same tissues as mrp/plf's but also the proteins expressed by these mmp genes are involved in similar physiological tissue remodeling events like wound healing.…”
Section: Regulation Of Gene Expression By the Fgf'smentioning
confidence: 96%
“…But if cJun-cFos heterodimers are present instead of cJun-cJun homodimers then a negative response is elicited in response to glucocorticoids [312]. PKC's induce cFos and cJun and it was shown that inhibiting PKC's did not have any effect on the bFGF regulation of mrp3 [313]. These experiments suggested that AP-1 is not involved in regulating mrp3 in response to bFGF stimulation.…”
Section: Regulation Of Gene Expression By the Fgf'smentioning
confidence: 96%
See 3 more Smart Citations